2016
DOI: 10.1177/2331216516657466
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Diagnostic Test for Hidden Hearing Loss

Abstract: Cochlear synaptopathy (or hidden hearing loss), due to noise exposure or aging, has been demonstrated in animal models using histological techniques. However, diagnosis of the condition in individual humans is problematic because of (a) test reliability and (b) lack of a gold standard validation measure. Wave I of the transient-evoked auditory brainstem response is a noninvasive electrophysiological measure of auditory nerve function and has been validated in the animal models. However, in humans, Wave I ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
86
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 39 publications
(64 reference statements)
0
86
0
3
Order By: Relevance
“…This was compared to an FFR for a low frequency pure tone (see Barker et al., 2014 for a preliminary use of this approach). The purpose of using such differential measures is to isolate the effects of synaptopathy from individual differences due to unrelated factors such as head size, and background physiological noise (see Plack et al, 2014, Plack et al., 2016 for further discussion).…”
Section: Introductionmentioning
confidence: 99%
“…This was compared to an FFR for a low frequency pure tone (see Barker et al., 2014 for a preliminary use of this approach). The purpose of using such differential measures is to isolate the effects of synaptopathy from individual differences due to unrelated factors such as head size, and background physiological noise (see Plack et al, 2014, Plack et al., 2016 for further discussion).…”
Section: Introductionmentioning
confidence: 99%
“…ABR amplitudes are highly variable, influenced by factors such as head size, cochlear dispersion, and skull thickness (Michalewski et al., 1980, Trune et al., 1988, Don et al., 1994), which might obscure the effects of synaptopathy. Differential ABR measures may minimize the influence of these non-synaptopathic factors (Plack et al., 2016), but recent evidence suggests a more fundamental shortcoming of the ABR. Recordings in gerbils and guinea pigs after ototoxic exposure indicate that AN fibers with the lowest SRs do not contribute to the compound action potential, equivalent to ABR wave I (Bourien et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Work in macaques further 3 suggested that mammals are more resilient to hair cell loss, but show similar vulnerability to 4 cochlear synaptopathy in comparison to most rodent models (Valero et al, 2017). Nevertheless, 5 the degree to which synaptopathy and the use of subcortical measures for diagnostics are 6 transferable to humans is still a topic of debate due to species-specific differences in the 7 physiology of hearing (Hickox et al, 2017;Plack et al, 2016;Prendergast et al, 2017). 8 Furthermore, humans show increased variation in physiological measures compared to animals 9 due to the heterogeneity in tissue-conductance, head size, cognitive abilities, noise exposure ).…”
Section: Introductionmentioning
confidence: 99%
“…Aging listeners with 7 impaired audiograms are thus likely to suffer from both OHC deficits and synaptopathy, 8 rendering the interpretation of electrophysiological metrics complicated as the metrics can be 9 affected by both deficits. The quantification and isolation of cochlear synaptopathy from other 10 coexisting contributors of hearing loss is therefore still a major unsolved problem in hearing 11 diagnostics (Hickox et al, 2017;Kobel et al, 2017;Plack et al, 2016;Verhulst et al, 2016). 12 As a first step to disentangle peripheral hearing deficits from a single electrophysiological 13 metric, we investigated whether existing ABR/EFR metrics for synaptopathy diagnosis in a young 14 NH (yNH) group (25±4.1 years) follow the same trends for an older hearing impaired (oHI) group 15 (65±7.9 years) with high-frequency sloping audiograms.…”
Section: Introductionmentioning
confidence: 99%